Single Nucleotide Mutagenesis of the TaCHLI Gene Suppressed Chlorophyll and Fatty Acid Biosynthesis in Common Wheat Seedlings - Wang, Chaojie; Zhang, Lili; Li, Yingzhuang; Ali Buttar, Zeeshan; Wang, Na; Xie, Yanzhou; Wang, Chengshe (Frontiers in Plant Science, 2020)
Wheat (Triticum aestivum L.) is one of the most important crops in the world. Chlorophyll, which is the major component in plant photosynthetic tissues, plays a vital role in plant development, crop improvement and further determines the crop productivity to a certain extent. The biosynthesis of chlorophyll remains a complex metabolic process, of which the leaf color mutants could be an effective resource to study the chlorophyll biosynthesis. In this study, we have identified a chlorophyll deficiency mutant, known as chli, from the wheat cultivar Shaannong33. chli exhibited obvious pale green leaf color at one-leaf stage with significantly decreased chlorophyll, Proto IX and Mg-Proto IX contents. Interestingly, a higher Proto IX to Mg-Proto IX ratio was observed in chli. The lipid biosynthesis in chli leaf and seed was also affected, displaying significantly reduced total lipid contents relative to Shaanong33. Genetic analysis indicated that the pale green leaf phenotype was controlled by a single pair of recessive nuclear gene. This mutant gene was mapped to an interval between 670-680 Mb on the wheat chromosome arm 7AL by SNP chip assay, within which the gene TraesCS7A01G480700.1 was predicted as the candidate target gene. Sequence alignment further revealed a single-nucleotide mutation (G664A) in the gene TraesCS7A01G480700.1 of chli which encoded I subunit of the Mg-chelatase in plants. This single-nucleotide mutation resulted in an amino acid substitution (D221N) in the highly conserved domain of the Mg-chelatase I subunit. As a result, mutant protein Tachli-7A lost the ability to interact with the normal protein TaCHLI-7A in Yeast two-hybrid assay. Meanwhile, Tachli-7A could not recover the chlorophyll deficiency phenotype of mutant Arabidopsis SALK_050029. Moreover, we found that Proto IX to Mg-Proto IX ratio in Shaannong33 was growth-state dependent and insensitive to environmental change in a short period under natural field condition. Taken together, mutation in Tachli-7A impaired the function of Mg-chelatase and blocked the conversion of Proto IX to Mg-Proto IX. Meanwhile, the phenotype of chli and the mutant site in Tachli-7A suggested that chli is a unique mutant for further study and understanding of the chlorophyll biosynthesis pathway in common wheat.